2014
DOI: 10.1016/j.immuni.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Treg Cells Expressing the Coinhibitory Molecule TIGIT Selectively Inhibit Proinflammatory Th1 and Th17 Cell Responses

Abstract: Summary Foxp3+ T regulatory (Treg) cells regulate immune responses and maintain self-tolerance. Recent work shows that Treg cells are comprised of many subpopulations with specialized regulatory functions. Here we identified Foxp3+ T cells expressing the co-inhibitory molecule TIGIT as a distinct Treg cell subset that specifically suppresses pro-inflammatory T helper 1 (Th1) and Th17 cell, but not Th2 cell responses. Transcriptional profiling characterized TIGIT+ Treg cells as an activated Treg subset with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
723
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 752 publications
(757 citation statements)
references
References 33 publications
(62 reference statements)
28
723
5
1
Order By: Relevance
“…Before examining a potential role for TIGIT in regulating antitumor T cell responses, we first examined the expression of TIGIT and its ligands on several Figure 3A and complete list in Supplemental Table 1). Many of these genes are consistent with those previously reported as differentially regulated in TIGIT + Tregs relative to TIGIT -Tregs in naive mice (12). Similarly upregulated genes included genes that encode coinhibitory receptors (Pdcd1, which encodes PD-1, Lag3, Ctla4, and Havcr2, which encodes TIM-3), chemokines and chemokine receptors (Ccr2, Ccr5, Ccr8, Cxcr3, Cxcr6, and Ccl5), transcription factors (Rora, Prdm1, Id2, Tbx21, and Foxp3), and the effector molecule Il10.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Before examining a potential role for TIGIT in regulating antitumor T cell responses, we first examined the expression of TIGIT and its ligands on several Figure 3A and complete list in Supplemental Table 1). Many of these genes are consistent with those previously reported as differentially regulated in TIGIT + Tregs relative to TIGIT -Tregs in naive mice (12). Similarly upregulated genes included genes that encode coinhibitory receptors (Pdcd1, which encodes PD-1, Lag3, Ctla4, and Havcr2, which encodes TIM-3), chemokines and chemokine receptors (Ccr2, Ccr5, Ccr8, Cxcr3, Cxcr6, and Ccl5), transcription factors (Rora, Prdm1, Id2, Tbx21, and Foxp3), and the effector molecule Il10.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, while TIGIT + CD8 + TILs exhibited deficits in proinflammatory cytokine production, we found that they had significantly increased production of the immune-suppressive cytokine IL-10 compared with TIGIT -CD8 + TILs. Moreover, we found that TIGIT + CD8 + TILs exhibited a reduced capacity to degranution to direct regulation of effector T cell responses, recent studies show that TIGIT marks a subset of Tregs that exhibit heightened expression of known Treg effector molecules and heightened suppressive capacity in vitro (12,14). Most interestingly, TIGIT + Tregs exhibit a specialized function, that of selectively suppressing proinflammatory Th1 and Th17 responses but sparing Th2 responses (12), thus supporting a role for TIGIT in directing Treg function.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…For example, the expression of TIGIT (T-Cell Immunoreceptor With Ig And ITIM Domains) has been found in tumour-infiltrating conventional CD4 + T-cells compared to circulating CD4 + Tcells 45 . It has been demonstrated that TIGIT contributes to the induction of a selective Treg-cell-mediated suppression of pro-inflammatory Th1 and Th17 cells but not Th2 cell responses 47 , thus it is possible that Th2 cells are not only recruited to the tumour site, but also promoted by evading TIGIT-mediated inhibition. The final explanation is that the production of IL-4, a classical Th2 cytokine, promote the differentiation of Th2 cells and inhibit IFN-g production by CD4 + T-cells 48 , therefore the secretion of this cytokine could also promote an enriched Th2 environment.…”
Section: Regulatory Cd4 + Th-like Helper Cells In Cancermentioning
confidence: 99%
“…TIGIT negatively regulates T cell responses through the effect of cluster of differentiation (CD) 112 or CD155 on dendritic cells or through intrinsic inhibitory effects such as inhibition of T cell proliferation or suppression of cytokine production in CD4 + T cells 14. Recently, TIGIT + Tregs have been shown to selectively suppress Th1 and Th17 responses but not Th2 responses 15. Moreover, TIGIT improves Th2 responses and allergic disease through the activity of CD155, whereas blockade of TIGIT with a neutralizing anti‐TIGIT antibody exerts a therapeutic effect on allergic airway inflammation in a murine model of asthma 16.…”
Section: Introductionmentioning
confidence: 99%